PERFORMANCE OF MAIZE (ZEA MAYS) GROWN ON MILDLY ACIDIC LOW FERTILE SOIL AS AFFECTED BY SELECTED ORGANIC-BASED SOIL AMENDMENTS AND SYNTHETIC FERTILIZER - P.A., Babajide; T. B., Akinrinola; Y.B., Oyeyiola; M.O., Okoro-Robinson; T.B., Salami; Adedayo, Adesina; A. A., Akindeere (International Journal of Research -GRANTHAALAYAH, 2018)
Under intensive cropping systems in the tropics, application of chemical fertilizers becomes an apparently indispensable means of replenishing the rapidly depleting soil nutrients. However, the reported side effects of continuous application of synthetic fertilizers on soil and man are now a major concern. Hence, determination of the potentials of some easily exploitable natural or organic-based fertilizer material(s), which can effectively compete with the commonly used synthetic fertilizers like NPK 15-15-15, is a worthwhile scientific approach, not towards improved performance of versatile arable crop like maize, but also for total eradication or alleviation of chemical inputs on tropical soils. A field experiment was conducted at the Teaching and Research Farms, Ladoke Akintola University of Technology (LAUTECH), Ogbomoso, in the year 2017, to comparatively determine the effects of NPK fertilizer and some selected organic-based fertilizer / ammendments on growth, yield and nutrient uptakes of maize (Zea mays). Six treatments were introduced, T0 (the control which received no fertilizer application), T1 (NPK fertilizer application), T2 (Tithonia compost application), T3 (Organomineral fertilizer application), T4 (Poultry manure application) and T5 (Cow dung application). All fertilizers were applied at recommended rates. The experiment was laid out in Randomized Complete Block Design (RCBD), replicated thrice. Data were collected on growth and yield parameters, and were subjected to analysis of variance. Means were separated using Duncan multiple range test. Application of different fertilizer materials significantly improved maize performance and nutrient uptakes, compared to the control. Organomineral fertilizer application produced the highest values of most of the growth and yield parameters measured. Although, the values obtained were mostly not significantly different from other fertilizer materials tested (except for cow dung, which was in some cases, significantly lower in values than other fertilizers tested, but significantly higher than the control (which steadily had the least values of all the parameters measured). Such significant increments may be due to the cherished attributes of organomineral fertilizer (some its nutritious fractions may be rapidly released while remaining fractions may be slowly released, over a long period of time). Hence, application of organomineral is therefore recommended. This will considerably reduce chemical loads on the soil in the study area. Meanwhile, in order to be purely organic in maize production, either composted tithonia or poultry manure is recommended for the study area. This will not only prevent total dependence on harmful and highly priced chemical fertilizers, but may promote improved soil nutrition and hygienic crop productivity.